Experimental Study on Compressive Strength, Flexural Strength, and Microstructure of Epoxy Mortar as Concrete Repair Mortar - Umbu Tay, Bonaventura Haryanto; Sutarja, I Nyoman; Widiarsa, Ida Bagus Rai (Journal of the Civil Engineering Forum, 2026)
his study investigates the potential of custom-formulated epoxy-based concrete repair mortar as an alternative material for structural applications. Conventional commercial mortars, while practical, often exhibit limitations in long-term strength and durability. This research evaluates the mechanical and microstructural performance of epoxy mortar using a self-mixed composition consisting of epoxy resin, cornice adhesive, and silica sand. Three variations were developed based on the ratio of epoxy resin to cornice adhesive (50%, 70%, and 100%), and were labeled as RE0.5, RE0.7, and RE1. A commercial epoxy–cement-based mortar, Sikafloor-81 Epocem (SF), was used as a benchmark for comparison. Specimens were prepared in the form of cubes and prisms and tested at curing ages of 7, 14, and 28 days for compressive and flexural strength. Microstructural characteristics were analyzed using X-ray fluorescence (XRF), X-ray diffraction (XRD), and scanning electron microscopy (SEM). At 28 days, the compressive strength values were 30.88 MPa for RE0.5, 48.56 MPa for RE0.7, 51.84 MPa for RE1, and 18.00 MPa for SF. Flexural strength results at 28 days reached 25.74 MPa (RE0.5), 31.18 MPa (RE0.7), 32.54 MPa (RE1), and 8.32 MPa (SF). Elemental analysis confirmed that the high silica content in the fine aggregate and the presence of calcium sulfate in the filler contributed to a denser and more rigid matrix. Crystalline phase analysis revealed quartz as the dominant structure, and microstructural observations indicated fewer pores and cracks in RE1 and RE0.7 compared to SF. These results indicate that a carefully optimized epoxy mortar formulation can exceed the performance of commercial products such as SF, offering enhanced mechanical strength and improved microstructural integrity for use in concrete repair.